Enterococcus spp.: Is It a Bad Choice for a Good Use—A Conundrum to Solve? - Mounir Ferchichi (MDPI AG, 2021)
Since antiquity, the ubiquitous lactic acid bacteria (LAB) Enterococci, which are just as predominant in both human and animal intestinal commensal flora, have been used (and still are) as probiotics in food and feed production. Their qualities encounter several hurdles, particularly in terms of the array of virulence determinants, reflecting a notorious reputation that nearly prevents their use as probiotics. Additionally, representatives of the Enterococcus spp. genus showed intrinsic resistance to several antimicrobial agents, and flexibility to acquire resistance determinants encoded on a broad array of conjugative plasmids, transposons, and bacteriophages. The presence of such pathogenic aspects among some species represents a critical barrier compromising their use as probiotics in food. Thus, the genus neither has Generally Recognized as Safe (GRAS) status nor has it been included in the Qualified Presumption of Safety (QPS) list implying drastic legislation towards these microorganisms. To date, the knowledge of the virulence factors and the genetic structure of foodborne enterococcal strains is rather limited. Although enterococcal infections originating from food have never been reported, the consumption of food carrying virulence enterococci seems to be a risky path of transfer, and hence, it renders them poor choices as probiotics. Auspiciously, enterococcal virulence factors seem to be strain specific suggesting that clinical isolates carry much more determinants that food isolates. The latter remain widely susceptible to clinically relevant antibiotics and subsequently, have a lower potential for pathogenicity. In terms of the ideal enterococcal candidate, selected strains deemed for use in foods should not possess any virulence genes and should be susceptible to clinically relevant antibiotics. Overall, implementation of an appropriate risk/benefit analysis, in addition to the case-by-case assessment, the establishment of a strain’s innocuity, and consideration for relevant guidelines, legislation, and regulatory aspects surrounding functional food development seem to be the crucial elements for industries, health-staff and consumers to accept enterococci, like other LAB, as important candidates for useful and beneficial applications in food industry and food biotechnology. The present review aims at shedding light on the world of hurdles and limitations that hampers the Enterococcus spp. genus and its representatives from being used or proposed for use as probiotics. The future of enterococci use as probiotics and legislation in this field are also discussed.